Early neonatal mortality and risk factors: a case-control study in Paraná State - Michelle Thais Migoto; Rafael Pallisser de Oliveira; Ana Maria Rigo Silva; Márcia Helena de Souza Freire
ABSTRACT Objective: to analyze the Early Neonatal Mortality risk factors according to the risk stratification criteria of the Guideline of the Rede Mãe Paranaense Program. Method: a case-control epidemiological study with secondary data from the Mortality and Live Birth Information System in 2014. The crude analysis was performed by the Odds Ratio association measure, followed by the adjusted analysis, considering risk factors as independent variables, and early neonatal death as dependent variable. Results: were considered as maternal risk factors: absence of partner and miscarriages; neonatal: male, low birth weight, prematurity, Apgar less than seven in the fifth minute, presence of congenital anomaly; and care: up to six prenatal appointments. Conclusion: an innovative study of risk factors for early neonatal death from the Guideline's perspective, a technological management tool for maternal and child health, in search of its qualification and greater sensitivity.